Pemberdayaan Ekonomi Keluarga melalui Penyuluhan Kewirausahaan dan Bisnis sebagai Motivasi dalam Upaya Peningkatan Kemandirian Berusaha - Mindari, Ellisyah; Asoka, Rano; Septariani , Jumania; Marsih, Yeni (Journal Of Human And Education (JAHE), 2024)
In order to establish family welfare, a variety of activities are used to try and chose and use the resources that are already available to meet economic demands. In an attempt to empower family economies to generate entrepreneurial motivation towards business independence, community service programs are being implemented with the goal of increasing literacy about entrepreneurship and business. This is because employees of government and organizational apparatuses possess low motivation and literacy about entrepreneurship and business. This activity makes use of lectures and debates as methods. The content is provided as instructional videos, written modules, and presentation slides. Participants are also required to complete solo exercises and assignments. This exercise involves giving presentations and having conversations based on the information that has been given (business and entrepreneurship; components of financial statements and bookkeeping procedures for entrepreneurs; entrepreneurship as a driving force for self-reliance). Participants' presence, a final assessment value gain over the beginning evaluation value, participants' excitement for the subject, and the occurrence of constructive exchanges during the discussion all contributed to the activity's good outcomes.